Older Breast Cancer Survivors: Factors Associated with Self-reported Symptoms of Persistent Lymphedema Over 7-years of Follow-up - Clough-Gorr, Kerri M. (2009)
INTRODUCTION: Lymphedema of the arm is a common complication of breast cancer with symptoms that can persist over long periods of time. For older women (over 50% of breast cancer cases) it means living with the potential for long-term complications of persistent lymphedema in conjunction with the common diseases and disabilities of aging over survivorship. METHODS: We identified women ≥65-years diagnosed with primary stage I-IIIA breast cancer. Data were collected over 7-years of follow-up from consenting patients’ medical records and telephone interviews. Data collected included self-reported symptoms of persistent lymphedema, breast cancer characteristics, and selected sociodemographic and health-related characteristics. RESULTS: The overall prevalence of symptoms of persistent lymphedema was 36% over 7-years of follow-up. Having stage II or III (OR=1.77, 95%CI 1.07–2.93) breast cancer and having a BMI>30 (OR=3.04, 95%CI 1.69–5.45) were statistically significantly predictive of symptoms of persistent lymphedema. Women ≥80-years were less likely to report symptoms of persistent lymphedema when compared to younger women (OR=0.44, 95%CI 0.18–0.95). Women with symptoms of persistent lymphedema consistently reported worse general mental health and physical function. CONCLUSION: Symptoms of persistent lymphedema were common in this population of older breast cancer survivors and had a noticeable effect on both physical function and general mental health. Our findings provide evidence of the impact of symptoms of persistent lymphedema on the quality of survivorship of older women. Clinical and research efforts focused on risk factors for symptoms of persistent lymphedema in older breast cancer survivors may lead to preventative and therapeutic measures that help maintain their health and well-being over increasing periods of survivorship.